Are we losing the battle against cardiometabolic disease? The case for a paradigm shift in primary prevention - Krämer Alexander; Kraushaar Lutz E (BMC, 2009)
Abstract Background Cardiovascular and diabetic disease are the leading and preventable causes of death worldwide. The currently prognosticated dramatic increase in disease burden over the next two decades, however, bespeaks a low confidence in our prevention ability. This conflicts with the almost enthusiastic reporting of study results, which demonstrate substantial risk reductions secondary to simple lifestyle changes. Discussion There is a case to be made for a disregard of the difference between statistical significance and clinical relevance of the reported data. Nevertheless, lifestyle change remains the main weapon in our battle against the epidemic of cardiometabolic disease. But along the way from risk screening to intervention to maintenance the compound inefficiencies of current primary preventive strategies marginalize their impact. Summary Unless we dramatically change the ways in which we deploy preventive interventions we will inevitably lose the battle. In this paper we will argue for three provocative strategy changes, namely (a) the disbanding of screening in favor of population-wide enrollment into preventive interventions, (b) the substitution of the current cost utility analysis for a return-on-investment centered appraisal of interventions, and (c) the replacement of standardized programs modeled around acute care by individualized and perpetual interventions.